Measures of respiratory function correlate with fatigue in ambulatory persons with multiple sclerosis. (18th December 2015) - Ray, Andrew D.; Mahoney, Martin C.; Fisher, Nadine M.
Abstract: Purpose : This article examines the association between measures of respiratory muscle function and fatigue in individuals with mild-to-moderate disability multiple sclerosis (MS). Methods : This was a cross-sectional study of 37 ambulatory volunteers with MS (28 F/9 M, 52.7 ± 10.2 years, Expanded Disability Status Scale [EDSS] = 3.5 ± 1.9). No patients withdrew from the study. Primary outcome variables included measures of respiratory function: maximal inspiratory (MIP) and expiratory pressures (MEP), forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1 ), maximal voluntary ventilation (MVV12 ); and a self-reported measure of fatigue: the Modified Fatigue Impact Scale (MFIS). Secondary measures included 6-min walking test (6MWT), a timed stair climb, the Short Form (SF)-36, the Epworth Sleepiness Scale and the Physical Activity and Disability Scale (PADS). Results : Significant correlations were shown between expiratory muscle strength (MEP) and the MFIS total ( p  < 0.03, r  = –0.362) and between MEP and physical fatigue scores ( p  < 0.03, r  = –0.360), as well as between MVV12 percent predicted (respiratory muscle endurance) and both the 6MWT ( p  = 0.045, r  = 0.346) and the Epworth Sleepiness Scale ( p  = 0.006, r  = 0.447). Conclusions : Respiratory muscle performance is correlated with perceived fatigue (MFIS), whereas respiratory endurance correlated to reductions in physical function and sleep quality among individuals with mild-to-moderate severity MS. Implications for Rehabilitation: Multiple sclerosis (MS) results in peripheral and respiratory muscle weakness and affected individuals report fatigue as one of their most disabling symptoms. Expiratory muscle strength was correlated with self-reported physical fatigue, while respiratory muscle endurance was correlated with functional performance and sleepiness. Respiratory muscle strength was not correlated with lung spirometry testing. These findings highlight the importance of considering the effects of respiratory muscle weakness when evaluating causes of fatigue among individuals with mild-to-moderate MS.